The Arens Algebras of Vector-Valued Functions. (23rd February 2014) - Ganiev, I. G.; Egamberdiev, O. I.
Abstract : A class of Arens algebras of vector Banach algebra valued functions is considered. It is shown that Arens algebra of vector-valued functions is complete locally convex metrizable algebra.